2021
DOI: 10.1017/pds.2021.416
|View full text |Cite
|
Sign up to set email alerts
|

Extended Taxonomy of Design and Innovation Games to Identify Perspectives of Development and Evaluation

Abstract: Learning innovation and design process is a necessity of the coming decade and games are a potential tool to do so. This paper proposes an extended taxonomy for categorising innovation and design games. The intent is to understand the essential, the similar and the different categories not only for development, but also for evaluation of innovation and design games, and in turn, help educators identify appropriate games for their learning objectives and curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Gamification can overcome significant problems like lack of learner's motivation, lack of interactivity, or isolation, leading to a high dropout rate in a course (Khalil and Ebner, 2014). The purpose of gamification can be served only when both the following are satisfied: (a) the Learning Objectives and outcomes are well defined; and (b) efforts are spent to assess the effect of gamification on those learning outcomes (Morschheuser et al, 2018;Bhatt et al, 2021b). Various empirical studies show that gamification has a positive effect on student interest, early engagement (Betts et al, 2013), and learning outcomes (e.g., retention rate) (Vaibhav and Gupta, 2014;Krause et al, 2015).…”
Section: Gamification and Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Gamification can overcome significant problems like lack of learner's motivation, lack of interactivity, or isolation, leading to a high dropout rate in a course (Khalil and Ebner, 2014). The purpose of gamification can be served only when both the following are satisfied: (a) the Learning Objectives and outcomes are well defined; and (b) efforts are spent to assess the effect of gamification on those learning outcomes (Morschheuser et al, 2018;Bhatt et al, 2021b). Various empirical studies show that gamification has a positive effect on student interest, early engagement (Betts et al, 2013), and learning outcomes (e.g., retention rate) (Vaibhav and Gupta, 2014;Krause et al, 2015).…”
Section: Gamification and Learningmentioning
confidence: 99%
“…Kirkpatrick's model consists of four levels of evaluation: reaction, learning, behavior, and result. With the help of this model, Bhatt et al (2021b) analyzed 20 games and classified them based on the levels of evaluation, and found that some existing games were not evaluated for their effectiveness on both learning and engagement. For example, the PDP game (Becker and Wits, 2014) and Innopoly (Berglund et al, 2011) only measure the effect of the game on learning but do not measure its ability to engage participants.…”
Section: Gamification and Learningmentioning
confidence: 99%
See 3 more Smart Citations